Evaluating oregano oil as a growth enhancer in nursery pig diets - C R Neill; C N Groesbeck; K R Lawrence; C W Hastad; R O Gottlob; B M Hildabrand; Jim L Nelssen; Michael D Tokach; Robert D Goodband; Joel M DeRouchey; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2004)
A total of 224 nursery pigs (PIC L 327L × C22) initially 12.9 ± 3.0 lb and 21 d of age were used in a 28-d feeding trial. The objective of our study was to evaluate the effects of oregano oil, with or without an in-feed antimicrobial. Oregano oil is a plant extract derived from the Greek herb, Origanum vulgare. It has been speculated to have antimicrobial-like activity. There were four dietary treatments in a 2 × 2 factorial. Diets consisted of a negative control (without an antibiotic or oregano oil), the control diet plus neomycin/oxytetracycline (140 g/ton), the control diet plus oregano oil, or the control diet with both neomycin/ oxytetracycline and oregano oil. The oregano oil (5%) was added to an inert carrier (95%) to make a premix that was added to the diet at 2 lb/ton in phase 1 (d 0 to 14) and 1 lb/ton in phase 2 (d 14 to 28). During the 28-d trial, neomycin/oxytetracycline improved ADG, ADFI and F/G. Pigs fed dietary treatments containing neomycin/oxytetracycline had the heaviest average weights at the end of the trial. Adding oregano oil to nursery pig diets did not improve ADG, ADFI, or F/G during the 28-d trial.; Swine Day, 2004, Kansas State University, Manhattan, KS, 2004
Keywords: Swine day; 2004; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 940; Kansas Agricultural Experiment Station contribution; no. 05-113-S; Nursery pigs; Neomycin/Oxytetracycline; Swine; Oregano; Pigs